Efek Variasi Temperatur Sintering Sebelum Leaching Terhadap Kandungan Silika yang Diekstrak dari Lumpur Teluk Kendari Menggunakan XRF (X-Ray Fluorescence) - Ferlyasari, Ferlyasari; Anas, Muhammad; Erniwati, Erniwati (Jurnal Penelitian Pendidikan Fisika, 2020)
This study aims to determine the effect of sintering temperature variations before leaching on the silica composition extracted from the Kendari Bay Clay. The research was carried out in the form of experimental research with stages, namely taking samples from the Kendari Bay Clay then the samples were washed with clean water and distilled water then filtered and dried in the sun for 24 hours. After drying, the sample was crushed and sieved with a 60 mesh, after that it was sintered in an electric furnace with temperature variations of 3000C, 5000C, 7000C and 9000C for 1 hour. The sample was leached with the solid-liquid extraction method in a 6 M HCl solution, stirred using a Magnetic Stirrer at a temperature of 1000C for 5 hours. Furthermore, the sample is filtered to get a residue then soaked using distilled water until the pH of water is neutral and dried in an oven with a temperature of 1000C for 5 hours. Analysis of the elemental composition and sample compounds using XRF (X-Ray Fluorescence). The results obtained showed that the variation of sintering temperature from 3000C to 7000C resulted in a colour change in the clay sample that was getting brighter and tended to increase the high purity silica content of 86.05% and could be used as a silica producer.Â